Community-Acquired Legionnaires Disease in Croatia: Clinical and Radiographic Evaluation - Višković, Klaudija (Array, 2010)
Legionella pneumophilla is well recognized etiologic factor in community acquired pneumonia. We analyzed the course of radiographic findings of 49 patients with Legionnaires' disease, correlated them with clinical and laboratory parameters and compared them with community acquired pneumonia caused by Mycoplasma pneumoniae, Chlamydophila pneumoniae and Coxiella burnetii .The most common radiographic finding at admission was unilobar, patchy infiltrate localized in the lower lobes. At follow up radiograph 4-12 days after admission, 42.9% of patients developed progression of infiltrates. A complete clearing of the infiltrates in the majority of patients (83.7%), was on the average noted on the 21st day of the onset of symptoms. The majority of patients with Legionnaires' disease presented with a clinically mild to moderate form and radiographic findings diferred from those seen in other atypical community acquired pneumonias.